Overhaul of solid construction locks in German federal waterways. Issue 1 (12th July 2019) - Carstensen, Norbert; Jäppelt, Ulrich; Willems, Hauke
Abstract : The predominant part of the navigable inland waterways in Germany was developed between the end of the nineteenth and the middle of the twentieth century. The main hydraulic structures of the barrages, such as weirs and navigation locks, were also built in this period. Meanwhile, these structures are aged but are still in operation. Thus, they have to be strengthened and repaired, and some of them have to be replaced with new structures. Furthermore, the locks have to be adapted according to the demands of modern inland navigation. Using the example of the double-chamber lock in Aldingen close to Stuttgart, the planning and execution of the overhaul of a concrete lock are described in this paper. The lock was built as part of a barrage on the River Neckar. While the construction of the lock had already started in the 1930s, the structure could not be completed until the end of the 1950s due to the Second World War. The repair of the solid construction is carried out through partial demolition of the chamber walls and the construction of reinforced-concrete facings on the chamber side of the walls.